Method for surface modification of carbon nanotube / silk fibroin composite film
By performing oxygen plasma, nitric acid or polydopamine surface modification treatment on the carbon nanotube film, combined with hot pressing treatment, the problem of insufficient binding of silk fibroin and carbon nanotubes is solved, and the mechanical properties and load transfer of the composite film are significantly improved. efficiency.
Patent Information
- Application Number
- CN202411248296.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-06
AI Technical Summary
During the preparation of the carbon nanotube/silicon fibroin composite film, the binding between the silk fibroin macromolecular segment and the carbon nanotube is weak, resulting in the mechanical properties of the composite film not reaching the expected level.
By performing oxygen plasma, nitric acid or polydopamine surface modification treatment on the carbon nanotube film, it enhances its interaction force with silk fibroin, and combines hot pressing treatment technology to improve the interface performance of the composite film.
The mechanical properties of the carbon nanotube/silicon fibroin composite film are significantly improved, and the interaction force and load transfer efficiency between the silk fibroin and carbon nanotubes are enhanced, forming a denser and excellent composite material.
Smart Images

Figure CN119119525A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon nanotube composite films, and in particular to a method for surface-modified carbon nanotube / silk fibroin composite films. Background Art
[0002] In recent years, carbon nanotube composite films have attracted widespread interest and great attention due to their unique mechanical, electromagnetic, optical, chemical and thermal conductivity properties. Based on their unique physical and chemical properties, carbon nanotube composite films have good potential application prospects in nanoelectronic devices, flat panel displays, electrochemical detection, sensors, pollutant separation and even tissue engineering materials.
[0003] Carbon nanotubes (CNTs) have highly crystalline and chemically inert surfaces. In the process of preparing carbon nanotube / silk fibroin (SF) composite films, it was found that the binding between the SF macromolecular segments and carbon nanotubes relies more on physical adhesion and the encapsulation and adhesion of the SF itself. When this binding mode is subjected to external forces, some SF macromolecular segments are easily detached from the carbon nanotube bundle, resulting in the mechanical properties of the composite film failing to reach the expected level. Therefore, it is urgent to develop a method for surface modification of carbon nanotube / silk fibroin composite films to enhance the mechanical properties of carbon nanotube / silk fibroin composite films. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a method for surface modification of carbon nanotube / silk fibroin composite film, which has low cost and strong operability.
[0005] The present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for surface-modified carbon nanotube / silk fibroin composite film, comprising the following steps:
[0007] (1) immersing a carbon nanotube film in chlorosulfonic acid (CSA), taking it out and applying a constant external force to the carbon nanotube film to stretch it, then removing excess chlorosulfonic acid, and performing a hot pressing treatment to obtain a pretreated carbon nanotube film;
[0008] (2) performing surface modification treatment on the pretreated carbon nanotube film obtained in step (1) to obtain a modified carbon nanotube film; the surface modification treatment is oxygen plasma surface modification treatment, nitric acid surface oxidation modification treatment or polydopamine surface modification treatment;
[0009] (3) dissolving the lyophilized silk fibroin powder in a solvent to obtain a silk fibroin solution; the solvent is formic acid, lithium bromide aqueous solution, hexafluoroisopropanol, dimethyl sulfoxide, trifluoroacetic acid or a calcium chloride-ethanol-water ternary system solution; immersing the modified carbon nanotube film obtained in step (2) in the silk fibroin solution, taking out the immersed carbon nanotube film and performing a hot pressing treatment to obtain a surface-modified carbon nanotube / silk fibroin composite film.
[0010] Surface modification and surface modification technology is a good post-treatment process for CNT films, which can effectively improve the interfacial properties of CNT films, increase the interaction between silk fibroin macromolecular chains and carbon nanotube bundles, and make the two more effectively and firmly combined together, so as to achieve the effect of improving the mechanical properties of CNT composite films.
[0011] The purpose of the present invention is to enhance the interaction between carbon nanotubes and silk fibroin to form a composite material with a denser structure and better performance. Three different surface modification processes, namely oxygen plasma surface modification, nitric acid surface oxidation modification and polydopamine surface modification, are used to improve the interface properties of CNT films and further improve the interaction force between SF-CNT and SF-SF and the load transfer efficiency.
[0012] Furthermore, in step (1), the organic solvent is selected from one or more of acetone, ethanol and benzene.
[0013] Furthermore, in step (1), the immersion time is 20 to 40 seconds.
[0014] Furthermore, in step (1), after taking out, a constant external force is applied to the carbon nanotube film within 20 to 40 seconds to stretch it to a deformation of 30 to 50%.
[0015] Furthermore, in step (1), the stretched carbon nanotube film is placed in an acetone solution to wash away the chlorosulfonic acid.
[0016] Furthermore, in step (1), the conditions for the hot pressing treatment are: hot pressing temperature is 140-160° C., pressure is 0.5-1.5 MPa, and time is 1-3 h.
[0017] Furthermore, in step (2), the method of oxygen plasma surface modification treatment is: placing the pretreated carbon nanotube film obtained in step (1) in a plasma treatment machine, and treating it at a power of 40 to 60 W for 150 to 200 seconds in an oxygen atmosphere to obtain a modified carbon nanotube film.
[0018] Furthermore, in step (2), the method for the nitric acid surface oxidation modification treatment is: immersing the pretreated carbon nanotube film obtained in step (1) in nitric acid, removing excess nitric acid, and obtaining a modified carbon nanotube film.
[0019] Furthermore, the immersion time is 1 to 3 hours.
[0020] Furthermore, after removing the excess nitric acid, a drying step is also included.
[0021] Furthermore, in step (2), the method for surface modification of polydopamine is: immersing the pretreated carbon nanotube film obtained in step (1) in a polydopamine aqueous solution, removing excess polydopamine, and obtaining a modified carbon nanotube film.
[0022] Furthermore, the polydopamine aqueous solution is prepared by the following method: dissolving dopamine hydrochloride in water, adding a pH adjuster to adjust the pH value to 8-9, and reacting to obtain the polydopamine aqueous solution.
[0023] Furthermore, the pH regulator is an alkaline compound, such as tris(hydroxymethyl)aminomethane (Tris), sodium hydroxide, etc.
[0024] Furthermore, the immersion time is 20 to 24 hours.
[0025] Furthermore, the concentration of polydopamine in the polydopamine aqueous solution is 1 to 5 g / L.
[0026] Furthermore, after removing excess polydopamine, a drying step is also included.
[0027] Furthermore, in step (3), the lyophilized silk fibroin powder is prepared by the following method:
[0028] S1. placing raw silk in a urea solution, performing two heat treatments, washing and drying to obtain urea degummed silk fibers;
[0029] S2. dissolving the silk fibers degummed by urea in a lithium bromide aqueous solution to obtain a silk fibroin / lithium bromide mixed solution;
[0030] S3. The silk fibroin / lithium bromide mixed solution was dialyzed using a dialysis bag with a molecular weight cutoff of 8000 to 14000Da, and a silk fibroin suspension was obtained after centrifugation;
[0031] S4. freeze-drying the silk fibroin suspension to obtain the silk fibroin freeze-dried powder.
[0032] Furthermore, in step (3), the concentration of silk fibroin in the silk fibroin solution is 1 to 7 wt %, preferably 3 to 7 wt %.
[0033] Furthermore, in step (3), the immersion time is 5 to 15 minutes, preferably 5 to 10 minutes.
[0034] Furthermore, in step (3), the conditions of the hot pressing treatment are: hot pressing temperature is 40-60° C., pressure is 3-5 MPa, and time is 20-40 min.
[0035] Furthermore, in step (3), after the hot pressing treatment, the step of placing the mixture at room temperature for 10 to 12 hours is also included.
[0036] The present invention also protects a surface-modified carbon nanotube / silk fibroin composite film prepared by the method.
[0037] Beneficial effects of the present invention:
[0038] The present invention adopts three different surface modification processes, namely oxygen plasma surface modification treatment, nitric acid surface oxidation modification treatment and polydopamine surface modification treatment, to improve the interface performance of the CNT film, further improve the interaction force between SF-CNT and SF-SF and the load transfer efficiency, thereby achieving the improvement of the mechanical properties of the carbon nanotube composite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The figures are the water contact angle test results of carbon nanotube films prepared by different surface modification methods; among them, (a) is CSA-CNT film, (b) is O-Plasma-CNT film, (c) is Nitric acid-CNT film, and (d) is PDA-CNT film.
[0040] Figure 2 Surface SEM images of carbon nanotube films prepared by different surface modification methods; among them, (a) and (b) are O-Plasma-CNT films, (c) and (d) are Nitric acid-CNT films, and (e) and (f) are PDA-CNT films.
[0041] Figure 3 Surface SEM images of carbon nanotube / silk fibroin composite films prepared by different surface modification methods; among them, (a) and (b) are CSA-CNT / SF composite films, (c) and (d) are O-Plasma-CNT / SF composite films, (e) and (f) are Nitric acid-CNT / SF composite films, and (g) and (h) are PDA-CNT / SF composite films.
[0042] Figure 4 At a strain rate of 1900s -1The following figure shows the dynamic mechanical properties test results of carbon nanotube / silk fibroin composite films prepared by different surface modification methods.
[0043] Figure 5 This is a graph showing the dynamic mechanical properties test results of carbon nanotube / silk fibroin composite films prepared by different surface modification methods under quasi-static conditions.
[0044] Figure 6 At a strain rate of 1900s -1 Tensile fracture morphologies of carbon nanotube / silk fibroin composite films prepared by different surface modification methods; (a), (b) and (c) are CSA-CNT / SF composite films, (d), (e) and (f) are O-Plasma-CNT / SF composite films, (g), (h) and (i) are Nitric acid-CNT / SF composite films, and (j), (k) and (l) are PDA-CNT / SF composite films. DETAILED DESCRIPTION
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0046] The present invention provides a method for preparing a carbon nanotube / silk fibroin composite film, comprising the following steps:
[0047] (1) immersing a carbon nanotube film in chlorosulfonic acid, taking it out and applying a constant external force to the carbon nanotube film to stretch it, then removing excess chlorosulfonic acid, and performing a hot pressing treatment to obtain a pretreated carbon nanotube film;
[0048] (2) performing surface modification treatment on the pretreated carbon nanotube film obtained in step (1) to obtain a modified carbon nanotube film; the surface modification treatment is oxygen plasma surface modification treatment, nitric acid surface oxidation modification treatment or polydopamine surface modification treatment;
[0049] (3) dissolving the lyophilized silk fibroin powder in formic acid to obtain a silk fibroin solution; immersing the modified carbon nanotube film obtained in step (2) in the silk fibroin solution, taking out the immersed carbon nanotube film and subjecting it to hot pressing to obtain a surface-modified carbon nanotube / silk fibroin composite film.
[0050] Wherein, the silk fibroin freeze-dried powder is prepared by the following method:
[0051] S1. placing raw silk in a urea solution, performing two heat treatments, washing and drying to obtain urea degummed silk fibers;
[0052] S2. dissolving the silk fibers degummed by urea in a lithium bromide aqueous solution to obtain a silk fibroin / lithium bromide mixed solution;
[0053] S3. The silk fibroin / lithium bromide mixed solution was dialyzed using a dialysis bag with a molecular weight cutoff of 8000 to 14000Da, and a silk fibroin suspension was obtained after centrifugation;
[0054] S4. freeze-drying the silk fibroin suspension to obtain the silk fibroin freeze-dried powder.
[0055] In the following examples, the lyophilized silk fibroin powder was prepared by the following method:
[0056] S1. 20 g of raw silk was placed in 600 mL of 8.0 mol / L urea solution, treated in a water bath at 90°C for 2 h, then treated again with the above urea solution under the same conditions for 1 h, washed thoroughly with warm water, and dried in an oven at 60°C to obtain urea-degummed silk fibers;
[0057] S2. 10 g of the urea-degummed silk fiber was dissolved in 200 mL of a 9.3 mol / L lithium bromide aqueous solution, and stirred at 60° C. for 60 min until the fiber was completely dissolved to obtain a silk fibroin / lithium bromide mixed solution;
[0058] S3. After the silk fibroin / lithium bromide mixed solution is cooled to room temperature, it is placed in a dialysis bag with a molecular weight cutoff of 8000-14000Da, and then dialyzed in 4°C deionized water for 72 hours, with the water changed every 8 hours. After centrifugation at a speed of 8000r / min for 10 minutes, a silk fibroin suspension is obtained;
[0059] S4. Place the silk fibroin suspension in a freeze dryer and freeze-dry for 48 hours to obtain the silk fibroin freeze-dried powder.
[0060] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0061] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0062] Example 1
[0063] A method for oxygen plasma surface modification of a carbon nanotube / silk fibroin composite film comprises the following steps:
[0064] (1) The carbon nanotube film was immersed in chlorosulfonic acid for 30 seconds. After being taken out, a constant external force was applied to the carbon nanotube film within 30 seconds to stretch it to a deformation of 40%, and then placed in an acetone solution to wash away the chlorosulfonic acid. After hot pressing at a temperature of 150°C and a pressure of 1 MPa for 2 hours on a hot press, a pretreated carbon nanotube (CSA-CNT) film was obtained.
[0065] (2) The pretreated carbon nanotube film obtained in step (1) is placed in a plasma treatment machine and treated at a power of 50 W for 180 s in an oxygen atmosphere to obtain an oxygen plasma surface-modified carbon nanotube (O-Plasma-CNT) film.
[0066] (3) dissolving the lyophilized silk fibroin powder in formic acid to obtain a 5 wt% silk fibroin solution; immersing the oxygen plasma surface-modified carbon nanotube film obtained in step (2) in the 5 wt% silk fibroin solution for 10 min, taking out the immersed carbon nanotube film, hot-pressing it on a hot press at a temperature of 50° C. and a pressure of 4 MPa for 30 min, and then placing it at room temperature for 12 h to obtain an oxygen plasma surface-modified carbon nanotube / silk fibroin (O-Plasma-CNT / SF) composite film.
[0067] Example 2
[0068] A method for modifying the surface of a carbon nanotube / silk fibroin composite film by oxidation with nitric acid comprises the following steps:
[0069] (1) The carbon nanotube film is immersed in chlorosulfonic acid for 30 seconds. After being taken out, a constant external force is applied to the carbon nanotube film within 30 seconds to stretch it to a deformation of 40%, and then placed in an acetone solution to wash away the chlorosulfonic acid. After hot pressing at a temperature of 150° C. and a pressure of 1 MPa for 2 hours on a hot press, a pretreated carbon nanotube film is obtained.
[0070] (2) Immersing the pretreated carbon nanotube film obtained in step (1) in nitric acid for 2 hours, and repeatedly rinsing with deionized water to remove excess nitric acid, thereby obtaining a carbon nanotube film modified by nitric acid surface oxidation (Nitric acid-CNT).
[0071] (3) Dissolving the lyophilized silk fibroin powder in formic acid to obtain a 5 wt% silk fibroin solution; immersing the carbon nanotube film surface-oxidized by nitric acid obtained in step (2) in the 5 wt% silk fibroin solution for 10 min, taking out the immersed carbon nanotube film, hot-pressing it on a hot press at a temperature of 50° C. and a pressure of 4 MPa for 30 min, and then placing it at room temperature for 12 h to obtain a carbon nanotube / silk fibroin (Nitric acid-CNT / SF) composite film surface-oxidized by nitric acid.
[0072] Example 3
[0073] A method for surface-modifying a carbon nanotube / silk fibroin composite film with polydopamine comprises the following steps:
[0074] (1) The carbon nanotube film is immersed in chlorosulfonic acid for 30 seconds. After being taken out, a constant external force is applied to the carbon nanotube film within 30 seconds to stretch it to a deformation of 40%, and then placed in an acetone solution to wash away the chlorosulfonic acid. After hot pressing at a temperature of 150° C. and a pressure of 1 MPa for 2 hours on a hot press, a pretreated carbon nanotube film is obtained.
[0075] (2) Immersing the pretreated carbon nanotube film obtained in step (1) in a polydopamine aqueous solution for 24 hours, repeatedly rinsing with deionized water to remove excess polydopamine, and drying in a vacuum oven at 60° C. overnight to obtain a polydopamine surface-modified carbon nanotube (PDA-CNT) film; the polydopamine aqueous solution is prepared by the following method: 1 g of dopamine hydrochloride particles are uniformly dissolved in 500 mL of deionized water, 0.6 g of Tris particles are added to adjust the solution pH to 8.5, and a polydopamine solution with a concentration of 2 g / L is prepared.
[0076] (3) dissolving the lyophilized silk fibroin powder in a formic acid solution to obtain a 5 wt% silk fibroin solution; immersing the carbon nanotube film modified with polydopamine obtained in step (2) in the 5 wt% silk fibroin solution for 10 min, taking out the immersed carbon nanotube film, hot pressing it on a hot press at a temperature of 50° C. and a pressure of 4 MPa for 30 min, and then placing it at room temperature for 12 h to obtain a carbon nanotube / silk fibroin (PDA-CNT / SF) composite film.
[0077] Comparative Example 1
[0078] A method for preparing a carbon nanotube / silk fibroin composite film comprises the following steps:
[0079] (1) immersing the carbon nanotube film in chlorosulfonic acid for 30 seconds, taking it out and applying a constant external force to the carbon nanotube film within 30 seconds to stretch it to a deformation of 40%, then placing it in an acetone solution to wash away the chlorosulfonic acid, and hot pressing it on a hot press at a temperature of 150° C. and a pressure of 1 MPa for 2 hours to obtain a pretreated carbon nanotube (CSA-CNT) film;
[0080] (2) Dissolving the lyophilized silk fibroin powder in formic acid to obtain a 5 wt% silk fibroin solution; immersing the pretreated carbon nanotube film obtained in step (1) in the 5 wt% silk fibroin solution for 10 min, taking out the immersed carbon nanotube film, and hot-pressing it on a hot press at a temperature of 50° C. and a pressure of 4 MPa for 30 min, and then placing it at room temperature for 12 h to obtain a carbon nanotube / silk fibroin (CSA-CNT / SF) composite film.
[0081] X-ray photoelectron spectroscopy (XPS) was used to test the element content of the carbon nanotube films prepared by different surface modification treatment methods. The test results are shown in Table 1:
[0082] Table 1
[0083] Atomic content / % C1s N1s O1s CSA-CNT film 88.49 2.14 9.37 O-Plasma-CNT film 77.61 2.11 20.28 Nitric acid-CNT film 82.79 5.35 11.86 PDA-CNT film 82.87 3.52 13.61
[0084] As can be seen from Table 1, after surface modification, the intensity of the N1s and O1s peaks increased, and the intensity of the C1s peak decreased significantly. After oxygen plasma surface modification, the intensity of the O1s peak increased significantly, and after nitric acid surface oxidation modification, the intensity of the N1s peak increased significantly, which shows that the bombardment of high-energy active particles such as oxygen plasma and electrons on the surface of the CNT film is very effective, so that a small amount of oxygen-containing particles remain in the nano-scale micro-pits, and nitric acid adheres a large number of oxygen-containing functional groups on the CNT bundles. The intensities of the N1s and O1s peaks of the samples treated with polydopamine surface modification have increased significantly, indicating that the polydopamine particles are evenly distributed inside the CNT film.
[0085] The water contact angles of carbon nanotube films prepared by different surface modification methods were tested. The test results are shown in Figure 1As shown, carbon nanotubes are hydrophobic, and the contact angle of CSA-CNT film is about 104°. After oxygen plasma surface modification, the CNT film is etched under the bombardment of high-energy active particles in oxygen plasma, and a large number of nano-scale micro-pits are generated, which significantly improves the interface performance of the CNT bundle surface. The contact angle of O-Plasma-CNT film is only 5.6°, which has super hydrophilic properties. After nitric acid surface oxidation modification, the CNT bundle is immersed in nitric acid for a long time, and a small amount of oxygen-containing functional groups are generated on the bundle surface, which improves the interface performance of the CNT film. The contact angle of the CNT film reaches 89°, and the wettability is enhanced. After polydopamine surface modification, a layer of nano-scale polydopamine particles is evenly coated on the CNT bundle, making the surface of the CNT bundle rough, improving the interface performance of the CNT film, and the water contact angle of the CNT film reaches 88°, and the wettability is enhanced, showing hydrophilicity.
[0086] Scanning electron microscopy (SEM) was used to characterize the morphology of carbon nanotube films prepared by different surface modification methods. Figure 2 As shown in the figure, the surface of the CNT bundle in the CNT film after oxygen plasma surface modification is very rough. This is because the oxygen plasma surface modification will cause the CNT bundle to be damaged, forming a rough surface morphology, and the CNTs that fall off after the damage of some CNT bundles will agglomerate with some impurities and adhere to the surface of the bundle; the surface of the CNT film treated with nitric acid surface oxidation modification did not change significantly, and only the reduction of impurities was observed; in the CNT film treated with polydopamine surface modification, it can be seen that the CNT bundles are evenly covered with a layer of polydopamine, and the bonding between polydopamine and CNT bundles is very tight, and some of the remaining polydopamine forms agglomerates between the bundles.
[0087] Scanning electron microscopy (SEM) was used to characterize the morphology of carbon nanotube / silk fibroin composite films prepared by different surface modification methods. Figure 3As shown, the CNT film after oxygen plasma surface modification is not well combined with silk fibroin, and the silk fibroin is not evenly distributed on the CNT bundle. The rough morphology of the CNT surface after oxygen plasma surface modification is not completely repaired by the silk fibroin, and a small amount of impurities agglomerate with the silk fibroin and adhere to the bundle surface under the action of the silk fibroin. Due to the obstruction of the impurity agglomerates, the silk fibroin cannot fully enter the interior of the CNT film, and its distribution inside the CNT film is uneven, resulting in poor filling of the gaps between the CNT bundles. In the carbon nanotube / silk fibroin film prepared after surface oxidation modification treatment with nitric acid, the silk fibroin and CNT bundles are well bonded, and the surface of the film is relatively flat and smooth. However, many oxygen-containing functional groups adhere to the CNT bundles under the action of nitric acid, and these oxygen-containing functional groups may fall off and dissolve into the silk fibroin solution, resulting in increased interaction forces between the CNT bundles and silk fibroin and between silk fibroin. Silk fibroin forms a thicker accumulation layer on the CNT bundles, and irregular cracks appear on the surface after drying. The surface of the carbon nanotube / silk fibroin film prepared after surface modification with polydopamine is relatively flat and smooth. The silk fibroin is well combined with the CNT bundle under the adhesion effect of polydopamine, and is very evenly and densely coated on the CNT bundle. Moreover, since polydopamine has a good adhesion effect on the CNT bundle and will not fall off, the silk fibroin will not form accumulation on the CNT bundle. At the same time, polydopamine is a nano-scale particle, which will not hinder the silk fibroin from entering the interior of the CNT film, and the gaps between the CNT bundles are also well filled.
[0088] The test was performed at a strain rate of 1900 s -1 The dynamic mechanical properties of the carbon nanotube / silk fibroin composite films (Examples 1 to 3) prepared by different surface modification treatment methods are shown in the following test results. Figure 4 The dynamic mechanical properties of the carbon nanotube / silk fibroin composite films (Examples 1 to 3) prepared by different surface modification treatment methods under quasi-static conditions were tested. The test results are shown in Figure 5 The dynamic fracture strength and specific energy absorption values of the carbon nanotube / silk fibroin composite film prepared by surface treatment of carbon nanotubes with polydopamine are 2138.74MPa and 104.01MJ / m 3, compared with the composite film without surface treatment in Comparative Example 1, the surface treatment efficiency of the composite film increased by 150.14% and 128.26% respectively, which is better than the carbon nanotube / silk fibroin composite film prepared by oxygen plasma surface modification and nitric acid surface oxidation modification. It is proved that polydopamine has good adhesion performance, enhances the interaction between silk fibroin and carbon nanotubes, enables silk fibroin to adhere more firmly and tightly to the carbon nanotube bundle, better exerts the uniform shear deformation and molecular stick-slip deformation of silk fibroin, and makes the load transfer between adjacent CNTs more effective. Although the surface treatment of nitric acid can enhance the dynamic mechanical properties of the carbon nanotube / silk fibroin-rich film, the thicker accumulation layer of silk fibroin reduces the load transfer efficiency between the outer silk fibroin and the inner carbon nanotube. When subjected to external force, relative sliding is easily generated between the outer silk fibroin and the inner carbon nanotube, so that the mechanical properties of the carbon nanotube / silk fibroin composite film cannot meet expectations. The carbon nanotube / silk fibroin composite film prepared by oxygen plasma surface modification treatment will cause damage to the surface of the carbon nanotube bundles and partial breakage of the bundles. Therefore, during dynamic testing, the sample breaks rapidly and exhibits lower dynamic mechanical properties.
[0089] At a strain rate of 1900 s -1 The tensile fracture morphology of carbon nanotube / silk fibroin composite films prepared by different surface modification methods is shown in Figure 2. Figure 6 As shown in the figure, the fracture surfaces of the carbon nanotube / silk fibroin composite films prepared by surface oxidation modification with nitric acid and surface modification with polydopamine are smoother than those of the corresponding films; the CNT bundles pulled out from the fracture surface of the carbon nanotube / silk fibroin composite film prepared by surface modification with oxygen plasma are longer but less in number. Although SF covers the CNT bundles more evenly, a large amount of SF causes the CNT bundles to aggregate together to form thicker CNT bundles, and a thick layer of SF accumulates on the surface of the film, which affects the tensile properties of the composite film to a certain extent; and the CNT bundles pulled out from the fracture surface of the carbon nanotube / silk fibroin composite film prepared by surface modification with polydopamine are not only slender but also very dense, indicating that SF is evenly distributed on the CNT bundles, so it exhibits better dynamic tensile properties, which is consistent with the data of the tensile test.
[0090] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A method for surface-modifying a carbon nanotube / silk fibroin composite film, characterized in that: The following steps are involved: (1) immersing a carbon nanotube film in chlorosulfonic acid, taking it out and applying a constant external force to the carbon nanotube film to stretch it, then removing excess chlorosulfonic acid, and performing a hot pressing treatment to obtain a pretreated carbon nanotube film; (2) performing surface modification treatment on the pretreated carbon nanotube film obtained in step (1) to obtain a modified carbon nanotube film; the surface modification treatment is oxygen plasma surface modification treatment, nitric acid surface oxidation modification treatment or polydopamine surface modification treatment; (3) dissolving the lyophilized silk fibroin powder in a solvent to obtain a silk fibroin solution; the solvent is formic acid, lithium bromide aqueous solution, hexafluoroisopropanol, dimethyl sulfoxide, trifluoroacetic acid or a calcium chloride-ethanol-water ternary system solution; immersing the modified carbon nanotube film obtained in step (2) in the silk fibroin solution, taking out the immersed carbon nanotube film and performing a hot pressing treatment to obtain a surface-modified carbon nanotube / silk fibroin composite film.
2. The method according to claim 1, characterized in that In step (2), the method of oxygen plasma surface modification treatment is: placing the pretreated carbon nanotube film obtained in step (1) in a plasma treatment machine, and treating it at a power of 40 to 60 W for 150 to 200 seconds in an oxygen atmosphere to obtain a modified carbon nanotube film.
3. The method according to claim 1, characterized in that In step (2), the method for nitric acid surface oxidation modification treatment is: immersing the pretreated carbon nanotube film obtained in step (1) in nitric acid, removing excess nitric acid, and obtaining a modified carbon nanotube film.
4. The method according to claim 3, characterized in that The immersion time is 1 to 3 hours.
5. The method according to claim 1, characterized in that In step (2), the method for surface modification of polydopamine is: immersing the pretreated carbon nanotube film obtained in step (1) in a polydopamine aqueous solution, removing excess polydopamine, and obtaining a modified carbon nanotube film.
6. The method according to claim 5, characterized in that The polydopamine aqueous solution is prepared by the following method: dissolving dopamine hydrochloride in water, adding a pH regulator to adjust the pH value to 8-9, and reacting to obtain the polydopamine aqueous solution.
7. The method according to claim 6, characterized in that The pH adjuster is a basic compound.
8. The method according to claim 5, characterized in that The immersion time is 20 to 24 hours.
9. The method according to claim 5, characterized in that The concentration of polydopamine in the polydopamine aqueous solution is 1-5 g / L.
10. A surface-modified carbon nanotube / silk fibroin composite film prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Carbon nano tube composite film and preparation method thereof
CN103435027A
Flexible composite conducting film and preparation method thereof
CN109401337A
Post-treatment method for greatly improving performance of carbon nanotube film and application
CN116281963A
High-strength and high-toughness carbon nanotube composite film as well as preparation method and application thereof
CN118063812A
Method and apparatus for modifying carbon nanotube using plasma
KR1020090006912A
Cited By
High-strength degradable silk fibroin composite bone bar and preparation method thereof
CN121197525A
